2008
DOI: 10.1146/annurev.cellbio.23.090506.123245
|View full text |Cite
|
Sign up to set email alerts
|

Prelude to a Division

Abstract: Accurate segregation of chromosomes during meiosis requires physical links between homologs. These links are usually established through chromosome pairing, synapsis, and recombination, which occur during meiotic prophase. How chromosomes pair with their homologous partners is one of the outstanding mysteries of meiosis. Surprisingly, experimental evidence indicates that different organisms have found more than one way to accomplish this feat. Whereas some species depend on recombination machinery to achieve h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
161
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 150 publications
(169 reference statements)
0
161
0
Order By: Relevance
“…Such considerations could help to explain why, in several situations, in two of the most robust cases of ''region-specific'' pairing, for the XY chromosomes of Drosophila and for ''pairing centers'' in C. elegans, specificity is conferred by clusters containing multiple nontandem repeats of short sequences (1,11). For Drosophila, where 50 copies of a Ͻ250-bp repeat are normally involved in pairing, it has further been shown that, when pairing site sequences are moved to locations where flanking homology is absent, eight copies are largely sufficient to confer detectable pairing but two copies are not (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such considerations could help to explain why, in several situations, in two of the most robust cases of ''region-specific'' pairing, for the XY chromosomes of Drosophila and for ''pairing centers'' in C. elegans, specificity is conferred by clusters containing multiple nontandem repeats of short sequences (1,11). For Drosophila, where 50 copies of a Ͻ250-bp repeat are normally involved in pairing, it has further been shown that, when pairing site sequences are moved to locations where flanking homology is absent, eight copies are largely sufficient to confer detectable pairing but two copies are not (1).…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, whole chromosomes pair via multiple interactions all along their lengths (1-9) or via any region present in duplicate copies (10). In other cases, pairing occurs preferentially or exclusively in particular localized regions (''pairing sites''), which tend to involve repeated sequences, specific proteins (for establishment and/or maintenance of pairing) and/or heterochromatic regions (characterized by a paucity of genes and a less ''open'' chromatin structure) (1,(11)(12)(13)(14)(15).In contrast to recombination-related processes that are known to involve protein-mediated Watson-Crick basepairing interactions between a ssDNA and a ssDNA or dsDNA partner, the fundamental basis for ''recombination-independent'' pairing remains mysterious. The most obvious possibility is direct DNA/DNA interactions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When the telomeres are clustered, centromeres are oriented in the opposite direction than the telomeres, resulting in a telomere-centromere polarization of the meiocyte nucleus. The presence of the bouquet coincides with pairing of homologous chromosomes (3,5). In plants, mammals, and fungi, chromosome pairing depends upon the progression of meiotic recombination (5-7).…”
mentioning
confidence: 99%